1)
1/8ab * a² = a²/8a³b
1/2a³ * 4b = 4b/2a³b
2)
3x/7m³n³ * 3n = 9xn/21m³n⁴
4y/3m²n⁴ * 7m = 28ym/21m³n⁴
3)
a + b/a - b * (a + b) = a² + 2ab + b²/a² - b²
вторую не надо
4)
3d/m - n * (m - n) = 3dm - 3dn/(m - n)²
5)
x/2x + 1 * (3x - 2) = 3x² - 2x/6x² - x - 2
x/3x - 2 * (2x + 1) = 2x² + x/6x² - x - 2
6)
a - b/3a + 3b * (a - b) = a² - 2ab + b²/3a² -3b²
a/a² - b² * 3 = 3a/3a² -3b²
7)
3a/4a - 4 * (5 - 5a) = 15a - 15a²/40a - 20 - 20a²
2a/5 - 5a * (4a - 4) = 8a² - 8a/40a - 20 - 20a²
8)
7a/b - 3 * (-b - 3) = -7ab -21a/9-b²
Выражения на которые я умножал записывай над дробью
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)
1/8ab * a² = a²/8a³b
1/2a³ * 4b = 4b/2a³b
2)
3x/7m³n³ * 3n = 9xn/21m³n⁴
4y/3m²n⁴ * 7m = 28ym/21m³n⁴
3)
a + b/a - b * (a + b) = a² + 2ab + b²/a² - b²
вторую не надо
4)
3d/m - n * (m - n) = 3dm - 3dn/(m - n)²
вторую не надо
5)
x/2x + 1 * (3x - 2) = 3x² - 2x/6x² - x - 2
x/3x - 2 * (2x + 1) = 2x² + x/6x² - x - 2
6)
a - b/3a + 3b * (a - b) = a² - 2ab + b²/3a² -3b²
a/a² - b² * 3 = 3a/3a² -3b²
7)
3a/4a - 4 * (5 - 5a) = 15a - 15a²/40a - 20 - 20a²
2a/5 - 5a * (4a - 4) = 8a² - 8a/40a - 20 - 20a²
8)
7a/b - 3 * (-b - 3) = -7ab -21a/9-b²
вторую не надо
Выражения на которые я умножал записывай над дробью